Implementasi Pembelajaran Aqidah Akhlak dalam Membentuk Karakter Religius Peserta Didik di MTs Sirojut Tholibin Simpang Raya Kabupaten Kuantan Singingi - Imam Andrianto; Tri Prasetiyo Utomo (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2023)
This study discusses the importance of planning, implementation, and evaluation of aqidah (faith) and akhlak (morality) education with a constructivist approach at MTs Sirojut Tholibin Simpang Raya, particularly at the 7th-grade level, which is considered a critical stage in shaping students' religious character. The research methodology employed in this study is a qualitative approach with a case study design, involving data collection through interviews, observations, and document analysis. The results of the study reveal the school's strong commitment to nurturing students' religious character. Focused lesson planning, relevant material selection, and interactive teaching methods have been successfully implemented. Teachers integrate principles of religious and moral education into their teaching using in-depth approaches such as discussions, reflections, and simulations. Learning evaluation encompasses various instruments, including written exams, practical projects, student behavior observations, self-reflection, and group discussions. This study underscores the significance of religious and moral education in shaping students' religious character amid increasingly complex moral challenges. With the applied constructivist approach, MTs Sirojut Tholibin Simpang Raya can serve as a strong example in religious character education.